THE POLICY OF SOCIAL PRIORITIES - S. L. Orlov; D. A. Lobanov (Russian Journal of Economics and Law)
The article views the genesis of transition from the practical bases of rigid liberal economy to the social policy of state priorities, which is more adequate and familiar to the Russian population.